2005
DOI: 10.1037/0002-9432.75.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of Authority Within Contemporary Social Work Practice in Managed Mental Health Care Organizations.

Abstract: This article examines how social workers may use their authority to create managed mental health care organizations that support the principles and values of professional social work practice. By exploring research and theoretical contributions from a multidisciplinary perspective, the author suggests ways that social workers may incorporate empowerment strategies into their organizational practices to create more socially responsible and humane mental health organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
0
8
0
1
Order By: Relevance
“…In a recent report on the difficulties of the social work profession, job demands included increasing paperwork, unmanageable caseloads, and problems with difficult clients, as well as staff shortages and reduced availability of adequate supervision (Center for Workforce Studies, NASW, 2006). At the same time, confusing legislation and concomitant guidelines have increased the conflicting and incompatible demands on social workers (Bransford, 2005). Previous literature on burnout has suggested that these demanding job conditions are significant antecedents of social worker burnout (Söderfeldt, Söderfeldt, & Warg, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent report on the difficulties of the social work profession, job demands included increasing paperwork, unmanageable caseloads, and problems with difficult clients, as well as staff shortages and reduced availability of adequate supervision (Center for Workforce Studies, NASW, 2006). At the same time, confusing legislation and concomitant guidelines have increased the conflicting and incompatible demands on social workers (Bransford, 2005). Previous literature on burnout has suggested that these demanding job conditions are significant antecedents of social worker burnout (Söderfeldt, Söderfeldt, & Warg, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, confusing legislation and concomitant guidelines have increased the number of conflicting and incompatible demands on social workers (Bransford, 2005).…”
Section: Burnout In Social Workmentioning
confidence: 99%
“…Their clinical notes and scientific literature are filled with personal and social details essential to understanding the patient’s insider perspective. Psychology examines a person’s behavior and experience “in its quest to identify, remediate and prevent mental and physical disorders.”19 (p1128) Social work often applies a holistic social justice perspective to practice that includes concepts of advocacy and empowerment 20. The ability to express, which was valued more highly by the psychologist and social worker group, is clearly fundamental when attempting to understand the life contexts that drive meaning within the patient’s insider world.…”
Section: Discussionmentioning
confidence: 99%